Policies and Practices of Family Friendliness. Time and Employment Relations in Knowledge Work - Håpnes, Tove; Rasmussen, Bente (Nordic Journal of Working Life Studies, 2011)
In Norway an ideology of gender equality and the universal welfare state has created generous leave arrangements for parents, both mothers and fathers, to make the combination of work and family possible.To recruit competent women and men, knowledge work organisations have to accommodate to working hours that are compatible with the responsibility for a family. In the knowledge economy in Norway we therefore find women and men with higher education trying to act out the ideals of gen- der equality at work and at home. In this paper we explore how family-friendly policies in knowledge work organisations result in family-friendly practices.We do this by analysing two R&D departments belonging to large Norwegian companies in the international market. Both had policies of gender equality and family friendly working time arrangements and career opportunities for women with reduced hours.We show how different employment relations and forms of organisation influenced the work and time practices of the research scientists. Using the concept of social contracts in em- ployment and a relational concept of time, we found that it was more difficult to realise the reduced hours in the organisation that took responsibility for the career and welfare of their employees in a long-term perspective because of the mutual trust and obligations in this relationship.The women in the organisation with more transactional relations where their employment was dependent upon the market and their short-term economic performance, were able to use their accounting system to reduce their hours.The young fathers in the same organisation who were not yet established as experts, could not use the accounting system to limit their hours like the senior women.They needed to work long hours on scientific publications to qualify as researchers to secure their employment. In Norway an ideology of gender equality and the universal welfare state has created generous leave arrangements for parents, both mothers and fathers, to make the combination of work and family possible.To recruit competent women and men, knowledge work organisations have to accommodate to working hours that are compatible with the responsibility for a family. In the knowledge economy in Norway we therefore find women and men with higher education trying to act out the ideals of gen- der equality at work and at home. In this paper we explore how family-friendly policies in knowledge work organisations result in family-friendly practices. We do this by analysing two R&D departments belonging to large Norwegian companies in the international market. Both had policies of gender equality and family friendly working time arrangements and career opportunities for women with reduced hours.We show how different employment relations and forms of organisation influenced the work and time practices of the research scientists. Using the concept of social contracts in em- ployment and a relational concept of time, we found that it was more difficult to realise the reduced hours in the organisation that took responsibility for the career and welfare of their employees in a long-term perspective because of the mutual trust and obligations in this relationship.The women in the organisation with more transactional relations where their employment was dependent upon the market and their short-term economic performance, were able to use their accounting system to reduce their hours.The young fathers in the same organisation who were not yet established as experts, could not use the accounting system to limit their hours like the senior women.They needed to work long hours on scientific publications to qualify as researchers to secure their employment.